2015
DOI: 10.1016/j.jinf.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

IP-10 differentiates between active and latent tuberculosis irrespective of HIV status and declines during therapy

Abstract: IP-10 distinguished with high accuracy active TB from LTBI irrespective of HIV infection and declined during anti-TB chemotherapy. Plasma IP-10 may serve as a diagnostic biomarker to differentiate between the stages of TB infection and for monitoring therapy efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
51
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 48 publications
12
51
4
Order By: Relevance
“…Serum levels of the chemokine IP-10 (CXCL10) have demonstrated diagnostic value in differentiating between active TB and LTBI and to decline with treatment [11, 20, 54, 55]. In contrast to these reports, despite significant differences in IP-10 levels between fast and slow responders in our study, baseline levels of IP-10 alone showed relatively low sensitivity as a predictor of response to treatment.…”
Section: Discussioncontrasting
confidence: 91%
“…Serum levels of the chemokine IP-10 (CXCL10) have demonstrated diagnostic value in differentiating between active TB and LTBI and to decline with treatment [11, 20, 54, 55]. In contrast to these reports, despite significant differences in IP-10 levels between fast and slow responders in our study, baseline levels of IP-10 alone showed relatively low sensitivity as a predictor of response to treatment.…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, increased IP-10 serum levels are part of the biomarker profile characterizing the early onset of RRs (12,13). Levels of IP-10 decline again during antireactional therapy (13), similar to what has been described during tuberculosis treatment (14). With respect to the humoral immune response, IgM directed against the M. leprae-specific phenolic glycolipid I (PGL-I), although not informative for the identification of RR onset (13), represents a useful biomarker for monitoring the efficacy of treatment of leprosy (reactions), since IgM levels drop when reactions are effectively subdued (13).…”
supporting
confidence: 55%
“…Therefore, to more accurately distinguish between these two stages, the selective combination of immune response genes has been under study. Among them, the protein levels of CXCL10 (IP-10; Tonby et al, 2015; Wergeland et al, 2015; Xiong et al, 2016; regulated under IFN-γ) and levels of mRNA Kim et al, 2015 or protein (Jeong et al, 2015; Lee et al, 2015a) for CXCL9, CXCL10, and CXCL11 have been pointed out by other researchers. These studies were mostly performed with blood mononuclear cells after stimulation with Mtb-specific antigens.…”
Section: Discussionmentioning
confidence: 94%
“…IFN-γ and CXCL10 (Holm et al, 2014; Latorre et al, 2014; Jeong et al, 2015; Tonby et al, 2015; Wergeland et al, 2015) are already well-known major biomarkers for TB. Our results are in agreement with those of previous studies, and are not surprising given that CXCL10 is known to be under the regulation of IFN-γ.…”
Section: Discussionmentioning
confidence: 99%